تقنيةeatit دور مجلس الإدارة في مراقبة تطبيق حوكمة الشركات في المؤسسة الجزائرية للأقمشة الصناعية وال - : غلاب فاتح (جامعة المسيلة, 2020)
ملخص: تهدف هذه الدراسة الى تبيين مساهمة مجلس الإدارة في التحكم السليم لممارسات حوكمة الشركات في المؤسسة الجزائرية للأقمشة الصناعية والتقنيةEATIT، وبعد الدراسة والتحليل توصلنا الى أن حوكمة الشركات مجموع القوانين والقواعد والمعايير التي تحدد العلاقة بين إدارة الشركة من ناحية والمساهمين وأصحاب المصالح من جهة أخرى. ومجلس الإدارة هو المسؤول الأول عن حوكمة الشركة من خلال تفعيل مبادئ حوكمة الشركات. في حين توصلنا إلى أن مجلس الإدارة الشركة محل الدراسة دور دوه إيجابي في التحكم السليم في تطبيق حوكمة الشركات. Abstract: This study aims to demonstrate the contribution of the Board of Directors to the proper control of corporate governance practices in the Algerian Foundation for Industrial and Technical Fabrics EATIT. After the study and analysis, we concluded that corporate governance is the sum of laws, rules and standards that define the relationship between the company's management on the one hand and the shareholders and stakeholders on the other hand. The Board of Directors is primarily responsible for corporate governance by activating corporate governance principles. While we found that the board of directors of the company under study has a positive role to play in proper control of corporate governance implementation.
Keywords: الكلمات المفتاحية: حوكمة الشركات، مجلس الإدارة، المساهمين وحقوق المساهمين، إدارة الشركة، الإفصاح والشفافية. ; Key words: corporate governance, board of directors, shareholders and shareholders' equity, company management, disclosure and transparency